A Comparative Overview of the Behavior of Coastal and Mountain Communities in Household Waste Management in Mamuju District - Miftah Chairani; Ridhayani Adiningsih; Abdul Ganing; Tisa Nurul Fadliyah (Miracle Journal of Public Health, 2025)
Solid waste generation in Indonesia reached 20 million tons in 2022, with household waste being the largest contributor at 39.98%. This study aims to compare household waste management behaviors between communities living in coastal and mountainous areas. This study uses a comparative quantitative research design with a cross-sectional approach. The total sample consisted of 225 respondents, comprising 150 respondents in the Tahaya-haya neighborhood and 75 respondents in the Ujung Bulo Wisata hamlet. The study was conducted in Tahaya-haya as a representation of mountainous areas and Karampuang Island as a representation of coastal island environments. Bivariate analysis showed a statistically significant difference in knowledge of household waste management between the communities of Tahaya-haya and Ujung Bulo Wisata (p = 0.001). Respondents in Tahaya-haya had a higher proportion of good and very good knowledge (90.6%) compared to Ujung Bulo Wisata (65.3%). Although all respondents in both areas showed a very good attitude (100%) towards waste management, this attitude was not fully reflected in actual practice. The most striking gap was seen in waste management actions, where Tahaya-haya showed better practices, while most respondents in Ujung Bulo Wisata were in the poor category. Recommendations for local governments to provide waste management infrastructure in coastal and mountainous areas.